Intrauterine Gardnerella vaginalis Infection Results in Fetal Growth Restriction and Alveolar Septal Hypertrophy in a Rabbit Model - Cheah, Fook-Choe; Lai, Chee Hoe; Tan, Geok Chin; Swaminathan, Anushia; Wong, Kon Ken; Wong, Yin Ping; Tan, Tian-Lee (Frontiers in Pediatrics, 2021)
Background: Gardnerella vaginalis (GV) is most frequently associated with bacterial vaginosis and is the second most common etiology causing intrauterine infection after Ureaplasma urealyticum. Intrauterine GV infection adversely affects pregnancy outcomes, resulting in preterm birth, fetal growth restriction, and neonatal pneumonia. The knowledge of how GV exerts its effects is limited. We developed an in vivo animal model to study its effects on fetal development. Materials and Methods: A survival mini-laparotomy was conducted on New Zealand rabbits on gestational day 21 (28 weeks of human pregnancy). In each dam, fetuses in the right uterine horn received intra-amniotic 0.5X102 colony-forming units of GV injections each, while their littermate controls in the left horn received sterile saline injections. A second laparotomy was performed seven days later. Assessment of the fetal pups, histopathology of the placenta and histomorphometric examination of the fetal lung tissues was done. Results: Three dams with a combined total of 12 fetuses were exposed to intra-amniotic GV, and nine fetuses were unexposed. The weights of fetuses, placenta, and fetal lung were significantly lower in the GV group than the saline-inoculated control group [mean gross weight, GV (19.8±3.8 g) vs control (27.9±1.7 g), p<0.001; mean placenta weight, GV (5.5±1.0 g) vs control (6.5±0.7 g), p=0.027; mean fetal lung weight, GV (0.59±0.11 g) vs control (0.91±0.08 g), p=0.002]. There was a two-fold increase in the multinucleated syncytiotrophoblasts in the placenta of the GV group than their littermate controls (82.9±14.9 vs 41.6±13.4, p<0.001). The mean alveolar septae of GV fetuses was significantly thicker than the control (14.8±2.8 µm vs 12.4±3.8 µm, p=0.007). Correspondingly, the proliferative index in the interalveolar septum was 1.8-fold higher in the GV group than controls (24.9±6.6 % vs 14.2±2.9 %, p=0.011). The number of alveoli and alveolar surface area did not vary between groups. Discussion: Intrauterine GV infection induces fetal growth restriction in association with trophoblastic dysfunction, with increased placental multinucleated syncytiotrophoblasts. Also, alveolar septal hypertrophy with cellular proliferation indicates fetal lung re-modeling consequent to GV infection. Conclusion: This intra-amniotic model could be utilized in future studies to elucidate the acute and chronic effects of GV intrauterine infections.